Континуальность традиции: базовые перспективы анализа стратификационных порядков - Ковалиско, Н. (Социология: теория, методы, маркетинг, 2008)
The basic prospects and specificity of stratification analysis are considered in the article. Essence is exposed and the review of fundamental class and non-class (grada tions) stratification orders are carried out. Possibilities of study of stratification orders: objectivism & subjectivism; structure & activity; constructed communities & real groups; positions & dispositions; constant & “unset” factors of stratification are analysed, as well as perspective of application of multidimensional analysis of in equa lities in the context of conceptual triad of “positions–disposition–practices (activity)”.